Case Study: Improving Heat Abatement Strategies for Lactating Dairy Cows in Southwest Kansas - L. Mendonca; A. Scanavez (Kansas Agricultural Experiment Station Research Reports, 2017)
Temperature loggers attached to intravaginal devices can be used to assess severity of heat stress in dairy cows. Vaginal temperature data collected using this method can be used to evaluate effectiveness of heat abatement systems. The goal for this study was to use vaginal temperature information to evaluate the impact of implementing new heat abatement strategies in order to minimize heat stress in lactating dairy cows. Vaginal temperature of cows from 2 dairies located in southwest Kansas were assessed during summers of 2014 and 2017. Dairy A improved the heat abatement systems in 2017, while Dairy B did not. Historical information of herd fertility was evaluated from 2012 to 2017 for both herds. In 2014, cows from Dairy A had greater vaginal temperature compared with Dairy B. The assessment conducted in 2017, after implementation of new heat abatement strategies, revealed that cows from Dairy A had comparable vaginal temperature to their counterparts from Dairy B. This indicates that the new cooling system minimized the effects of heat stress. Moreover, fertility of Dairy A in the summer of 2017 was improved compared with previous years. Herd fertility during the summer was better in Dairy B than Dairy A from 2012 to 2016. In contrast, Dairy B had poorer fertility than Dairy A in 2017. These data suggest that fertility of dairy herds may be positively impacted by reducing heat stress through improved cooling systems.
Keywords: vaginal temperature; heat abatement; reproduction; heat stress